Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 57937 species occurrences available in GBIF matching the query: { "and" : [ "Geometry POLYGON((-6.726379 43.026737,-6.726379 42.524748,-5.998535 42.524748,-5.998535 43.026737,-6.726379 43.026737))", "HasGeospatialIssue is false" ] } The dataset includes 57937 records from 100 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001617-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences